Precise identification of a human immunodeficiency virus type 1 antigen processing mutant. - Zimbwa, P; Milicic, A; Frater, J; Scriba, T; Willis, A; Goulder, P; Pillay, T; Gunthard, H; Weber, J; Zhang, H; Phillips, R (2007)
Human immunodeficiency virus type 1 (HIV-1) evokes a strong immune response, but the virus persists. Polymorphisms within known antigenic sites result in loss of immune recognition and can be positively selected. Amino acid variation outside known HLA class I restricted epitopes can also enable immune escape by interfering with the processing of the optimal peptide antigen. However, the lack of precise rules dictating epitope generation and the enormous genetic diversity of HIV make prediction of processing mutants very difficult. Polymorphism E169D in HIV-1 reverse transcriptase (RT) is significantly associated with HLA-B*0702 in HIV-1-infected individuals. This polymorphism does not map within a known HLA-B*0702 epitope; instead, it is located five residues downstream of a HLA-B*0702-restricted epitope SPAIFQSSM (SM9). Here we investigate the association between E169D and HLA-B*0702 for immune escape via the SM9 epitope. We show that this single amino acid variation prevents the immune recognition of the flanked SM9 epitope by cytotoxic T cells through lack of generation of the epitope, which is a result of aberrant proteasomal cleavage. The E169D polymorphism also maps within and abrogates the recognition of an HLA-A*03-restricted RT epitope MR9. This study highlights the potential for using known statistical associations as indicators for viral escape but also the complexity involved in interpreting the immunological consequences of amino acid changes in HIV sequences.